Saving lives: assessing knowledge and attitudes toward basic life support among teachers and parents in Tabuk City - Alatawi, Amirah M. (Frontiers in Medicine, 2025)
BackgroundAssessing the current awareness levels of teachers and parents about basic life support is essential for identifying training gaps, obstacles to acquiring basic life support skills, and areas that require improvement.AimThis study aimed to evaluate the knowledge, skills, and attitudes concerning basic life support among kindergarten and primary school teachers and parents in Tabuk City, Saudi Arabia.MethodsThis cross-sectional survey was conducted in Tabuk City, Saudi Arabia, involving teachers and parents of children enrolled in kindergartens or elementary schools, aged 18 years or older. Data were collected using a previously validated, self-administered Arabic questionnaire, distributed through an online link via social media Apps. The total knowledge and skills score was then calculated.ResultsMost participants (70.3%) were parents, with ages ranging from 18 to 70 years and an average age of 35.1 ± 10.91 years. Female participants (59.7%) outnumbered males. Over half (53.3%) had no prior cardiopulmonary resuscitation (CPR) training, and 55.6% had never witnessed CPR being performed. Approximately half (50.3%) demonstrated a fair level of knowledge, while 44.6% had poor levels, and only 5.1% achieved a good level. A significant association was found between previous CPR training and knowledge and skill levels (p < 0.001). Additionally, the majority (81.0%) expressed interest in receiving further CPR training.ConclusionThis study identified substantial gaps in basic life support awareness and training among kindergarten and primary school teachers and parents in Tabuk City, Saudi Arabia. Most participants exhibited either poor or average levels of knowledge, with critical deficiencies in CPR skills. Prior exposure to CPR training was significantly associated with higher knowledge and skill scores, underscoring the importance of accessible and structured training programs. The main barrier to training was a lack of awareness of available CPR courses. Nevertheless, the high level of expressed interest in future training highlights a strong potential for improving BLS competency through targeted educational initiatives.